KEBIJAKAN PENDIDIKAN INKLUSIF BERDASARKAN HUKUM POSITIF DAN IMPLIKASINYA BAGI PENYANDANG DISABILITAS - Mohammad Syafril Rinaldy hulalata (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2025)
This study aims to analyze inclusive education policies in Indonesia from the perspective of positive law and their implications for fulfilling the rights of persons with disabilities. The research employs a normative legal method using statutory and conceptual approaches, combined with descriptive-analytical analysis of policy implementation effectiveness. The findings reveal that although Indonesia’s legal framework guarantees inclusive education, its implementation remains hindered by weak technical regulations, limited affirmative funding, a shortage of special education teachers, and inadequate disability-friendly facilities. The gap between legal norms and practical realities demonstrates that the right to education for persons with disabilities has not been substantively realized. Therefore, detailed technical regulations governing service standards, funding mechanisms, and supervision are urgently needed to ensure the effective implementation of equality and non-discrimination principles.